Microdomains in the cardiovascular system - Nikolaev, Viacheslav; Zaccolo, Manuela (Springer, 2017)
The book comprehensively presents new findings in cardiovascular research related to signaling microdomains in health and disease. Important second messengers such as cAMP, cGMP, calcium and their role in microdomain signaling are discussed. The book offers and explains methodical approaches and technical ways how to successfully analyze microdomain signaling, also in the context of disease. It further provides scientific perspectives and strategies that are based on the concept of signaling within microdomains and that can revolutionize pharmacology and eventually lead to the effective treatment of cardiovascular diseases in future. This book is written for scientists in cardiovascular research, pharmacology, molecular and cellular biology as well as medical doctors in cardiology, angiology and nephrology.
Keywords: Cardiovascular system -- Physiology.; Cardiovascular system -- Molecular aspects.; Human physiology.; Cytology.; Pharmacology.; elektronické knihy; electronic books